Aflatoxin in raw peanut kernels marketed in Malaysia. - Arzandeh, Sahar; Selamat, Jinap; Lioe, Hanifah Nuryani (National Laboratories of Foods and Drugs, 2010)
The occurrence of af latoxin in eighty-four samples of raw peanut kernels which are randomly collected from Malaysian super- markets was examined. Analysis for af latoxin was performed by solvent extraction and immunoaffinity clean-up followed by the determination using high performance liquid chromatography equipped with post-column photochemical reactor for enhanced detection and f luorescence detector. A detection limit of 0.01-0.09 ng/mL and a quantification limit of 0.04-0.30 ng/mL were obtained. The af latoxin concentrations ranged from not detected to 97.28 ng/g in all samples investigated. About 78.57% of the samples were contaminated with af latoxin, of which 10.71% exceeded the maximum tolerable limit of 15 ng/g set by the Codex. Average recoveries of the af latoxin analysis were acceptable which were in the range of 74.85 ± 8.83% for AFG2 at the concentration of 0.15 ng/mL and 103.91 ± 6.45% for AFB2 at the concentration of 0.15 ng/mL. The average daily intake estimated for total af la- toxins was 10.69 ng/kg body weight. There was a significant difference (P < 0.05) in af latoxin content between brands and locations.